PTU-077 Association between crohn's disease activity and therapeutic drug monitoring of thiopurines and infliximab comparing free and total antidrug antibody measurement. (22nd June 2015) - Warner, BD; Ward, MG; Johnston, EL; Irving, PM
Abstract : Introduction: Therapeutic drug monitoring (TDM) of infliximab (IFX) is useful in patients with Crohn's disease (CD). Therapeutic cut-offs to predict active disease and the influence of thiopurines on drug levels (DL) according to 6-thioguanine nucleotide (TGN) are not defined. There is limited data on the utility of free anti-drug antibodies (ADAb) against total ADAb. We assessed the utility of TDM of IFX in CD using a commercially available ELISA and investigated the influence of TGNs on DL and free/total ADAb. Method: Prospective evaluation of trough DL and ADAb using Lisa-Tracker, ((LT), Theradiag, France) and Immundiagnostik ELISA, ((IM), Germany) in 79 CD patients (male = 40) between January and May 2014. Only free ADAb is detected with LT assay, whereas IM assay measures total ADAb (semiquantitative). Total ADAb results were calculated using the cut off control. Results of TDM were assessed with respect to faecal calprotectin (FC), C-reactive protein (CRP) and clinical activity (Harvey Bradshaw Index, (HBI) <5 remission). The relationship between TGN and DL/ADAb was also assessed. LT kits were provided by Theradiag. Results: Higher DL were observed amongst patients in remission (HBI <5 DL 4.7 vs 1.7 μg/mL (p = 0.01), CRP <5 mg/L DL 5 vs 2.5 μg/mL (p = 0.007), FC <250 μg/g DL 5.6 vs 2.9 μg/mL (p = 0.001), FC <59 μg/g DL 5.8 vs 3.3 μg/mL (p = <0.001)). ROC curve analysis including thresholds to detect active disease are shown in Table 1 . ADAb were detected in 3 (4%) patients using LT vs 19 (24%) using IM assay. All patients with ADAb with LT had undetectable DL and had active disease on FC59. Total ADAb with IM assay did not correlate with outcomes. Concomitant immunomodulation use was associated with absence of ADAb using IM assay (p = 0.03), however a therapeutic TGN (>245 pmol/8 × 10 8 ) was not associated with ADAb (p = 0.5). TGN quartile analysis did not identify a value associated with DL (p > 0.5), nor was a therapeutic TGN associated with higher DL (p = 0.7). Conclusion: IFX DL were inversely related to disease activity. A cut-off of 3.0–5.7 μg/mL was associated with active disease depending on the definition used. The presence of free ADAb was associated with active inflammation, whereas the presence of total ADAb was not. There was no relationship between TGN and DL or ADAb, although most patients were adequately dosed. This study highlights the limitations and utility of TDM in IBD. Disclosure of interest: B. Warner: None Declared, M. Ward: None Declared, E. Johnston: None Declared, P. Irving Speaker Bureau of: AbbVie, MSD, Takeda, Warner Chilcott, Shire, Ferring and Tillotts Pharma.